„My heart was sick and sore with longing”. On the subject of male longing for love in Friedrich Hebbel’s letters to his wife Christine - Hindinger, Barbara (Transfer. Reception Studies, 2022)
Friedrich Hebbel (1813-1863) left behind an extensive correspondence, which is still not researched in detail. There are letters to his wife Christina (22.02.1852-26.03.1852) which deal with male longing and exceptional kind of love. The descriptions of longing not only show an alternative and emotional masculinity, but also a gender relationship which contradicts the conventional social ideas of the 19th century.